Examining factors that influence subordinates’ willingness to connect with supervisors on Facebook through the lens of communication privacy management theory - Akin, Kazim Yigit (Kansas State University, 2017)
Over the last decade, people have been able to access and use the Internet quickly and easily though several types of advanced technologies. Social networking sites (SNS) have attracted millions of users from all over the word and have become a part of their social and work lives. As the most popular SNS, Facebook.com has been leading the SNS market with 1.86 billion monthly active users (Facebook, 2017). Facebook has also been adopted by workplaces. Individuals in the workplace use Facebook for several reasons, such as staying in touch with colleagues. This integration of SNSs into people’s work life has led to personal and professional boundaries being blurred and created privacy dilemmas. This study examines factors that influence subordinate’s willingness to accept a Facebook friend request from their supervisor, using the theoretical lens of communication privacy management (CPM). Overall, 231 individuals who have a Facebook account and work at either a full-time or part-time job completed an online survey. A positive relationship was found between subordinates’ willingness to accept a Facebook friend request from a supervisor and subordinate communication satisfaction with a supervisor. This study’s results indicate that alterations in Facebook content, and being more open through privacy management practices do not predict subordinates’ willingness to accept supervisors’ Facebook friend request. Further, subordinates’ communication satisfaction with their supervisor did not influence subordinates’ content alterations of Facebook, such as deleting previously posted media content, wall posts, modifying profile information, or removing status updates. This thesis ends with a discussion of the implications of Facebook connections between subordinates and supervisors. This study also provides insights on the intersections of use of SNS, workplace use of SNSs, workplace relationships, and communication privacy management theory.
Keywords: Supervisor-subordinate communication; Facebook; Privacy management